Data Protection in Limbo: Regulatory Challenges in the Absence of an Implementing Authority in Indonesia - Sihombing, Andreas Bonardo (LPPM Institut Pendidikan Nusantara Global, 2025)
Data protection is a critical issue globally, and Indonesia's Personal Data Protection Law (PDP Law) of 2022 marks a major legal development. This study examines regulatory challenges stemming from the absence of an implementing supervisory authority mandated by the law. Employing qualitative doctrinal research and policy analysis, the study analyzes legal texts, institutional policies, and stakeholder interviews. The population includes government agencies, legal bodies, and private organizations involved with personal data management, with purposive sampling of relevant experts. Data were analyzed thematically to identify institutional gaps and enforcement issues. Findings reveal a regulatory vacuum caused by the lack of an independent supervisory authority, resulting in enforcement weaknesses, diminished public trust, and legal uncertainties. The study concludes that establishing a functional, autonomous authority is essential to enhance regulatory coherence, business compliance, and Indonesia's international data governance standing. Recommendations include formal institutionalization, financial sustainability, and multi-sectoral coordination.